Fano resonated, ultrathin, flexible and ultrawideband absorption featured nano-metaatom structure with dispersion gap optimized for optical range applications - Ahasanul Hoque; Mohammad Tariqul Islam; Ali F. Almutairi (Scientific Reports)
Abstract This article reports an Ultra wideband nano scale metamaterial absorber with ultrathin and flexible feature for visible spectrum applications. The absorber investigated for dispersion and Fano resonance characteristics to achieve metamaterial properties as well as independent of asymmetry of structure. Maximum visible spectrum wave interaction with the cascaded split nano square meta atom also ensured to achieve the absorption at highest percentage in numerical evaluation. The Finite Difference Time Domain (FDTD) method incorporated with CST microwave studio computational tool used for the entire analysis. Numerical analysis revealed that, on average 86.66% absorption achieved for 560 THz bandwidth peak absorption for the unit cell was 99.88% and the array shows 99.79%. Dispersion gap optimized based on mode 4 to incorporate all photons for phase and group velocity inside the nano metamaterial absorber. Furthermore, the Fano resonance wave to identify the high-quality factor at visible spectrum on nanostructure meta atom and direct-indirect visible wave trapped in the structure. The dispersion gap optimization and Fano resonance make the proposed cascaded split nano square meta atom a significant candidate for visible spectrum applications like solar energy harvesting, biochemical sensing, optical range application etc.